Fear of Missing Out (FOMO) in University Students: Informational Challenges and Implications for Digital Literacy - Ibáñez Marco , Marta; Martínez Cardama, Sara (Revista General de Información y Documentación, 2024)
This study investigates the impact of the "Fear of Missing Out" (FOMO) phenomenon on university students, focusing on their information habits, self-identification levels, and the extent of their knowledge regarding how social media present and organize information through algorithms. The sample comprised 205 students aged between 18 and 25 who participated in an online survey on social media and FOMO. The study highlights a direct connection between excessive mobile phone use and FOMO, particularly in terms of loss of concentration and sleep disorders. Respondents associated this issue more with social aspects than with information overload or other informational disorders. However, a low awareness was detected regarding the identification of underlying mechanisms that personalize and present information on social media. Raising awareness about algorithmic mechanisms and integrating the connection between FOMO and digital well-being into digital literacy programs is emphasized as a critical element in developing competency programs and the role of libraries and information professionals in this endeavor.
Keywords: FOMO; Digital literacy; social media; survey; university students